Hubungan Kepatuhan Kunjungan Antenatal Care (ANC) dengan Kemampuan Personal Hygiene Masa Nifas Pada Ibu Postpartum - Ziqro, Silviana; Indriyani, Diyan; Kholifah, Siti (Indonesian Journal Publisher, 2025)
Background: Antenatal care (ANC) is essential in helping mothers maintain personal hygiene during the postpartum period. Non-compliance with ANC visits may reduce understanding of hygiene and increase infection risk. Objective: This study aimed to explore the association between compliance with ANC visits and postpartum mothers' personal hygiene practices. Method: A quantitative study with a cross-sectional correlational design was employed. on 70 postpartum mothers who delivered vaginally, selected via total sampling. Data were collected using a questionnaire and analysed with the Chi-Square test at α = 0.05 Results: A significant association was found between ANC compliance and personal hygiene (p < 0.001). An OR of 40.25 showed that compliant mothers were 40 times more likely to practise good hygiene. Conclusion: Compliance with ANC visits improves postpartum mothers' hygiene.